Effect of Patient Characteristics on Treatment Decisions Regarding Keratinocyte Carcinoma in Elderly Patients: A Review of the Current Literature - Marjolijn S. Haisma; Linda Bras; Mehran Alizadeh Aghdam; Jorrit B. Terra; Boudewijn E.C. Plaat; Emöke Rácz; Gyorgy B. Halmos (Medical Journals Sweden, 2020)
There are straightforward guidelines for treatment of keratinocyte carcinoma (formerly known as non-melanoma skin cancer); however, there are no clear recommendations specifically for elderly patients. The aim of this review was to provide an overview of the current literature about the effect of patient characteristics, specifically life expectancy, frailty and comorbidity, on treatment decisions in elderly patients with keratinocyte carcinoma, by searching PubMed database. It was found that the literature is limited and based mostly on small retrospective studies. Therefore, it is difficult to give firm recommendations about how to treat elderly people who have keratinocyte carcinoma. A "one-size-fits-all" approach to this population is not sufficient: life expectancy and frailty need to be considered in the decision-making process regarding treatment for elderly people with keratinocyte carcinoma. Among the comorbidity scores, Adult-Comorbidity-Evaluation-27-index seems to have the best prognostic value. Prospective studies are needed to generate more individualized recommendations for this increasing and often vulnerable group.